2019
DOI: 10.1002/pros.23887
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycine‐N‐acyltransferase like 1 (GLYATL1) in prostate cancer

Abstract: Background Recent microarray and sequencing studies of prostate cancer showed multiple molecular alterations during cancer progression. It is critical to evaluate these molecular changes to identify new biomarkers and targets. We performed analysis of glycine‐N‐acyltransferase like 1 (GLYATL1) expression in various stages of prostate cancer in this study and evaluated the regulation of GLYATL1 by androgen. Method We performed in silico analysis of cancer gene expression profiling and transcriptome sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…GLYATL1 encodes an enzyme with phenylacetyl-CoA glutamine N-acyltransferase activity, which regulates mitochondrial ATP production, glycine availability, CoASH availability, and the detoxification of various organic acids ( 50 ). In a previous study, the expression of GLYATL1 was higher in localized prostate cancers than in benign prostatic tissue and metastatic prostate cancer ( 49 , 51 ). This study also demonstrated that GLYATL1 may be associated with the grade of prostate cancer since the expression of GLYATL1 was significantly high in low-grade tumors.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…GLYATL1 encodes an enzyme with phenylacetyl-CoA glutamine N-acyltransferase activity, which regulates mitochondrial ATP production, glycine availability, CoASH availability, and the detoxification of various organic acids ( 50 ). In a previous study, the expression of GLYATL1 was higher in localized prostate cancers than in benign prostatic tissue and metastatic prostate cancer ( 49 , 51 ). This study also demonstrated that GLYATL1 may be associated with the grade of prostate cancer since the expression of GLYATL1 was significantly high in low-grade tumors.…”
Section: Discussionmentioning
confidence: 77%
“…These findings suggest that FANCI has a novel oncogenic role and may be useful as a prognostic biomarker and/or therapeutic target for different tumors. GLYATL1 belongs to the glycine-N-acyltransferase gene family and is normally expressed in the liver and kidney ( 49 ). GLYATL1 encodes an enzyme with phenylacetyl-CoA glutamine N-acyltransferase activity, which regulates mitochondrial ATP production, glycine availability, CoASH availability, and the detoxification of various organic acids ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enriched genes such as SULT1A2 [Fernandez-Santander et al 2013], PIK3C2G [Li et al 2015], AGL (amylo-alpha-1, 6-glucosidase, 4-alpha-glucanotransferase) [Richmond et al 2018], UGT2B10 [Lu et al 2018], CTH (cystathionine gamma-lyase) [Xu et al 2020] and CYP26A1 [Osanai and Lee, 2015] were involved in metabolic activity of various cancer types, but these genes may liable for metabolic activity of in hepatoblastoma. Enriched genes such as TDO2 [Pham et al 2018], EPHX2 [Vainio et al 2011], PLA2G2A [Ganesan et al 2008], INPP1 [Li et al 2019], GCH1 [Gao et al 2016], GNE (glucosamine (UDP-N-acetyl)-2-epimerase/N-acetylmannosamine kinase) [Kemmner et al 2012], PAPSS2 [Zhang et al 2019], GLYATL1 [Eich et al 2019], CFB (complement factor B) [Kim et al 2019], C1R [Riihilä et al 2020], C1S [Riihilä et al 2020], C9 [Chong et al 2010], FGB (fibrinogen beta chain) [Repetto et al 2018] and KNG1 [Quesada-Calvo et al 2017] were linked with development of various cancer types, but these genes may be culpable for advancement of hepatoblastoma. Methylation inactivation of tumor suppressor enriched genes such as HAAO (3-hydroxyanthranilate 3,4-dioxygenase) [Huang et al 2010] and AOX1 [Vantaku et al 2019] were identified with growth of various cancer types, but loss of these genes may be liable for progression of hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…GLYATL1 is involved not only in normal physiological metabolism but also in tumorigenesis. A previous study demonstrated that the mRNA expression of GLYATL1 was unregulated by androgen and ETS variant transcription factor 1 (ETV1) in prostate cancer (10). Moreover, Kishimoto and colleagues showed that the protein expression of GLYATL1 in HCC tissues was lower than that in non-tumor tissues (9).…”
Section: Introductionmentioning
confidence: 99%